PENGARUH LAJU ALIR TUNGSTEN IN-ERT GAS TERHADAP KEKUATAN TARIK DAN KEJUT PADA SAMBUNGAN LAS TIG BAJA GALVANIS DAN ALU-MINIUM 5052 DENGAN FILLER AL-SI 4043 - Redi Bintarto; Moh. Syamsul Ma’arif; Denny Widhiyanuriyawan; Teguh Dwi Widodo; Rudianto Raharjo; Nugroho Adi Purnomo (Jurnal Rekayasa Mesin, 2023)
This study aims to determine the effect of the protective gas flow rate on the tensile and shock strength of welded joints of dissimilar metals, namely aluminum 5052 – galvanized steel with Al-Si 4043 filler using argon gas as a shielding gas. The protective gas flow rate parameters used in this study were 14, 17, and 20 liters/minute with a current of 80 A. The results showed that the higher the flow rate of the shielding gas, the lower the porosity defects that occurred in the welding results, resulting in higher tensile and shock strength values. Based on the analysis through the results of penetrant testing, it shows that the addition of the protective gas flow rate is given to reduce the porosity defects in the welding area. The surface area experiencing porosity decreases with the addition of the protective gas flow rate of 14, 17, and 20 liters/minute of 59.748%, 50.918%, and 48.857% respectively. The highest tensile strength was obtained from welding with a protective gas flow rate of 20 liters/minute of 20.01 MPa, then a protective gas flow rate of 17 liters/minute of 16.32 MPa, and the lowest at a protective gas flow rate of 14 liters/minute of 10 ,44 MPa. The highest shock strength is obtained from welding with a protective gas flow rate of 20 liters/minute of 0.5644 mJ/mm2, then a protective gas flow rate of 17 liters/minute of 0.4048 mJ/mm2, and the lowest is a gas flow rate protection 14 liters/minute of 0.2981 mJ/mm2.